2009
DOI: 10.1104/pp.109.141499
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Mapping of Nutrient Uptake in the Rhizosphere Using Nanoscale Secondary Ion Mass Spectrometry

Abstract: Plant roots and microorganisms interact and compete for nutrients within the rhizosphere, which is considered one of the most biologically complex systems on Earth. Unraveling the nitrogen (N) cycle is key to understanding and managing nutrient flows in terrestrial ecosystems, yet to date it has proved impossible to analyze and image N transfer in situ within such a complex system at a scale relevant to soil-microbe-plant interactions. Linking the physical heterogeneity of soil to biological processes marks a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 27 publications
0
92
0
Order By: Relevance
“…Although adequate sample preparation remains challenging, imaging mass spectrometry via NanoSIMS represents a promising avenue for mapping the spatial organisation, metabolic pathways and resource fluxes within cells, plants and at the root-fungus-soil interface, in particular in labelling studies (e.g. Clode et al, 2009). …”
Section: Nano-scale Secondary Ion Mass Spectrometers (Nanosims)mentioning
confidence: 99%
“…Although adequate sample preparation remains challenging, imaging mass spectrometry via NanoSIMS represents a promising avenue for mapping the spatial organisation, metabolic pathways and resource fluxes within cells, plants and at the root-fungus-soil interface, in particular in labelling studies (e.g. Clode et al, 2009). …”
Section: Nano-scale Secondary Ion Mass Spectrometers (Nanosims)mentioning
confidence: 99%
“…1C and D). 8 It was shown that introduced 15 N could be detected, and more importantly, mapped, in individual bacterial cells found in the soil matrix, within the rhizosphere, within root hairs, and intra-cellular within the root. 15 n/ 14 n ratio image from nanoSimS of the same bacteria.…”
Section: Uptake Of Amino Acids By Plants and Microorganismsmentioning
confidence: 99%
“…Internal structures of the root were visible, as well as the chemical composition of the minerals at the root surface. Further examples for NanoSIMS, a similar technique with much higher resolution, can be found in Clode et al (2009). While ToFSIMS is able to identify the entire atomic mass range in a single run, NanoSIMS requires that masses of interest be selected prior to the measurement.…”
Section: Chemical Imaging Challenges and Opportunitiesmentioning
confidence: 99%